Analysıs Of Factors Influencıng Customers' Desıre To Contınue Usıng Bnı Mobıle Bankıng Servıces - Muhammad Tegar Baihaqi; Erlita Ridanasti (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study aims to find evidence of factors that influence a person's desire to continue using BNI mobile banking services. This research focuses on six variables including contact, communication, perceived entertainment, perceived gamification, perceived value of m-banking, and desire to reuse m-banking. The research method used in this research is quantitative research. The data used in this study are primary data totaling 125 respondents. The data collection technique was carried out through an online questionnaire. Data analysis in this study used PLS-SEM. The results showed that all hypotheses proposed in this study were accepted.